1997
DOI: 10.1210/jcem.82.5.3949
|View full text |Cite
|
Sign up to set email alerts
|

Routine Measurement of Plasma Calcitonin in Nodular Thyroid Diseases

Abstract: In a prospective study, plasma concentrations of human calcitonin (hCT) were determined in 1062 consecutive patients with thyroid nodular disease. Basal plasma hCT was above the normal range (Ͼ6 pg/mL) in 55 patients and was elevated up to more than 100 pg/mL (range, 127-5459) in 3 of these 55 patients. A pentagastrin-induced rise in hCT up to more than 100 pg/mL was observed in only 1 of 38 patients with a basal concentration of hCT between 5-10 pg/mL, but was found in 10 of 31 patients with basal hCT ranging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
61
0
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 13 publications
(20 reference statements)
2
61
0
9
Order By: Relevance
“…It occurs in 5-10% of thyroid tumors (1) and has a prevalence of between 0.3 and 1.37% in nodular thyroid disease (2)(3)(4)(5)(6)(7)(8)(9). Calcitonin (C T ) is a marker for both initial diagnosis and monitoring of patients with residual or recurrent MTC (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It occurs in 5-10% of thyroid tumors (1) and has a prevalence of between 0.3 and 1.37% in nodular thyroid disease (2)(3)(4)(5)(6)(7)(8)(9). Calcitonin (C T ) is a marker for both initial diagnosis and monitoring of patients with residual or recurrent MTC (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Serum C T assays are indicated in nodular thyroid patients if there is a family history of MTC, multiple endocrine neoplasia type 2, or non-defined thyroid cancer (1). In Europe, several researchers have recommended the systematic use of serum C T assays in all nodular thyroid patients, in order to identify sporadic MTC as early as possible (2)(3)(4)(5)(7)(8)(9), optimize surgical treatment (12), and obtain better survival (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, two diagnostic tools are available for the evaluation of patients with NTD, including those with MTC: FNAC and measurement of human C t concentrations. Previous European studies recruiting large series of patients with NTD (6)(7)(8)(9)(10)(11)(12) demonstrated that it is possible to diagnose MTC earlier with C t screening than FNAC, particularly in patients with nodules smaller than 10 mm (microMTCs). Hence, the ETA has recommended C t screening in all subjects with NTD (13).…”
Section: The Thyroid Isthmus and The Parafollicular C Cellsmentioning
confidence: 99%
“…Several studies (6)(7)(8)(9)(10)(11)(12) on sporadic MTC have demonstrated that the earlier the diagnosis the better the prognosis of MTC. C t has been shown to represent a sensitive marker for MTC, leading to the early diagnosis of the neoplasm even when fine needle aspiration cytology (FNAC) discloses benign features (as occurs in nodules smaller than 10 mm).…”
Section: Introductionmentioning
confidence: 99%